IMPROVING WATERPROOFING PROPERTIES IN THE WALL BASEMENT AREA BY INJECTION METHOD (Academic journal Industrial Machine Building Civil Engineering, 2019)
The article is focused on the natural experimental research of injection waterproofing impact on basement areas of existingbuildings brick walls. Two types of experimental installations for waterproofing material injection have been developed. Thesecond type turned out to be more efficient due to the fact that it could cover larger waterproofing wall area. It can possiblyspeed up the process of walls waterproofing and major repairs of buildings in general. According to the experimental data, after the injection waterproofing placement, the wall moisture content decreased by half due to the high quality waterproofingmaterial and performed installation work.
Keywords: construction; moisture content; injection waterproofing; major repairs; wall basement area